A canine model of human aging and Alzheimer's disease() - Head, Elizabeth (2013)
The aged dog naturally develops cognitive decline in many different domains (including learning and memory) but also exhibits human-like individual variability in the aging process. The neurobiological basis for cognitive dysfunction may be related to structural changes that reflect neurodegeneration. Molecular cascades that contribute to degeneration in the aging dog brain include the progressive accumulation of beta-amyloid (Aβ) in diffuse plaques and in the cerebral vasculature. In addition, neuronal dysfunction occurs as a consequence of mitochondrial dysfunction and cumulative oxidative damage. In combination, the aged dog captures key features of human aging, making them particularly useful for the development of preventive or therapeutic interventions to improve aged brain function. These interventions can then be translated into human clinical trials. This article is part of a Special Issue entitled: Animal Models of Disease.